A apropriação da linguagem escrita pela criança e a organização do ensino das características sonoras da a palavra para a alfabetização: contribuições da teoria histórico-cultural - Possamai, Lidiane (2022)
This research was developed in the Postgraduate Program in Education, Master's level, at the State University of Western Paraná (Unioeste), Francisco Beltrão campus (PR), in the research line Culture, Educational Processes and Teacher Training, being also linked to the Group of Studies and Research on Teaching, Learning and Cultural-Historical Theory (GEPEATH). The theme was literacy and the object of the research was the appropriation of written language by the child. It was assumed that written language is one of the most important tools for access to knowledge and cultural goods developed by mankind. It contributes to the production of meaning by the subject (a condition that affects and results in the formation of personality), to the operation and regulation of psychic functions, and to the development of forms of behavior. It is directly linked to the development of oral language and requires knowledge about the writing system, which in the case of the Portuguese language is alphabetic. The fundamental principle of the Alphabetic Writing System (AES) conceives writing as a graphic-visual representation of speech sounds. From this perspective, teaching about the sound aspects of the word for children's literacy presents itself as a necessity for effective knowledge about the AES and for the progressive mastery of reading and writing. Considering these elements, the following guiding question was established for this research: How to work pedagogically with the sound characteristics of the word in the children's literacy process? This question is based on the interest in understanding a literacy proposal that contributes to the appropriation of reading and writing by the child and that considers these aspects. In order to shed light on this problematic, the Historical-Cultural Theory (THC) was defined as a theoretical reference, whose theoretical and epistemological bases are found in the Historical-Dialectical Materialism method (MHD). In its nature, this is a bibliographical research based mainly on Vygotski (1984, 1995), Vygotski (2009), Luria (1979, 1986, 2017), Leontiev (2004, 2017) and Elkonin (1987, 1989, 2009). As results, it was understood that the sound aspects of the word are a necessary and indispensable component for children's literacy, which is legitimized by the commitment to ensure the appropriation of written language as a promoter of human development and intellectual emancipation of the subjects, since the reading and writing practices enable a new way to access knowledge and the production of meanings about reality and the multiple phenomena of life. Considering the assumptions of THC, the sound characteristics of the wordcan be enhanced in the initial reading teaching process through tasks proposed by the sound analysis method of the word developed by Elkonin (1987). However, the implementation of this method in the Brazilian school system requires a deeper study of the characteristics of the Portuguese language, the elements that regulate education in the country and the objective conditions of teacher training and work.